2014
DOI: 10.1021/ja502280w
|View full text |Cite
|
Sign up to set email alerts
|

Congested C–C Bonds by Pd-Catalyzed Enantioselective Allyl–Allyl Cross-Coupling, a Mechanism-Guided Solution

Abstract: Under the influence of a chiral bidentate diphosphine ligand, the Pd-catalyzed asymmetric cross-coupling of allylboron reagents and allylic electrophiles establishes 1,5-dienes with adjacent stereocenters in high regio- and stereoselectivity. . A mechanistic study of the coupling utilizing reaction calorimetry and density functional theory analysis suggests that the reaction operates through an inner-sphere 3,3'-reductive elimination pathway, which is both rate- and stereodefining. Coupled with optimized react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(51 citation statements)
references
References 78 publications
1
47
0
2
Order By: Relevance
“…1c) may interact with the C3–C4 π cloud, placing the nucleophilic Cγ near the dienoate C6. This pathway would be reminiscent of a 3,3′-reductive elimination proposed vis-à-vis enantioselective allyl–allyl coupling with Ni- and Pd complexes 17,18 . A similar reaction mode with an organocopper species has been mentioned in just one instance (again, without experimental or computational support) 19 .…”
mentioning
confidence: 99%
“…1c) may interact with the C3–C4 π cloud, placing the nucleophilic Cγ near the dienoate C6. This pathway would be reminiscent of a 3,3′-reductive elimination proposed vis-à-vis enantioselective allyl–allyl coupling with Ni- and Pd complexes 17,18 . A similar reaction mode with an organocopper species has been mentioned in just one instance (again, without experimental or computational support) 19 .…”
mentioning
confidence: 99%
“…2 Recently, our group has disclosed a number of methods that employ chiral, small-bite-angle bidentate phosphine ligands to reverse the regioselectivity of these couplings to give branched 1,5-dienes of type C with excellent regio- and enantioselectivity (eq 2). 3 Recent mechanistic and computational studies 4 have supported previous proposals 3 that the reaction is operative through an inner-sphere 3,3′-reductive elimination 5 , in which coupling at carbons 3 and 3′ through the conformation as shown in B leads to the branched isomer. These studies are in line with computational studies on the preferred reductive elimination pathways for unsubstituted allylic systems by Eschavarren 5a and Espinet 5c , which also found the 3,3′-reductive elimination to be preferred over direct coupling at the 1 and 1′ carbons.…”
Section: Introductionmentioning
confidence: 67%
“…Unlike iridium and molybdenum catalysts, palladium has a natural propensity to form linear allylation products . However, it was reported that small‐bite‐angle ligands drive the allylpalladium equilibrium towards the formation of primary organopalladium species and this observation was cleverly used for the preparation of stereodefined vicinal tertiary and quaternary carbon stereogenic centers with BYPHEP L 3 as ligand (Scheme ) . Using substituted allylboronic esters and allyl chloride derivatives, the method proceeds with excellent regio‐ and enantiocontrol yet with a modest diastereoselectivity.…”
Section: Allylic Substitutionmentioning
confidence: 99%